2014
DOI: 10.1155/2014/528517
|View full text |Cite
|
Sign up to set email alerts
|

A New Proposal for Learning Curve of TEP Inguinal Hernia Repair: Ability to Complete Operation Endoscopically as a First Phase of Learning Curve

Abstract: Background. The exact nature of learning curve of totally extraperitoneal inguinal hernia and the number required to master this technique remain controversial. Patients and Methods. We present a retrospective review of a single surgeon experience on patients who underwent totally extraperitoneal inguinal hernia repair. Results. There were 42 hernias (22 left- and 20 right-sided) in 39 patients with a mean age of 48.8 ± 15.1 years. Indirect, direct, and combined hernias were present in 18, 12, and 12 cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…The learning curve for any particular procedure is defined as the minimum number of cases needed to acquire adequate surgical skills and knowledge of pitfalls and technical aspects of the procedure with minimum operative time and decrease in complication rates. [9][10][11] In literature, various cutoff limits for the learning period of laparoscopic hernia repair have been recommended, reaching up to a minimum of 250 cases being regarded as comfort zone. 7 In another review, performing atleast 30 to 100 operations was suggested as a critical threshold level to become experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve for any particular procedure is defined as the minimum number of cases needed to acquire adequate surgical skills and knowledge of pitfalls and technical aspects of the procedure with minimum operative time and decrease in complication rates. [9][10][11] In literature, various cutoff limits for the learning period of laparoscopic hernia repair have been recommended, reaching up to a minimum of 250 cases being regarded as comfort zone. 7 In another review, performing atleast 30 to 100 operations was suggested as a critical threshold level to become experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…14 Appropriate patient selection is an important parameter for successful surgery during the early period of learning. 3 In the early period, TEP hernia repair may prudently avoid irreducible hernias and patients with previous lower quadrant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 Since this technique does not require entry into the abdominal cavity and it is free from complications related to abdominal cavity entry, it has gained popularity in the recent two decades. 3 Advantages of TEP hernia repair include equivalent recurrence rates as the open technique with less neural pain, less hematoma occurrence, lower infection rate and short recovery period. Compared to TAPP hernia repair, TEP hernia repair has a shorter operation time and less possibility of damaging adjacent organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] However, the learning curve of TEP hernioplasty is long and steep, and carries paramount importance for the beginners/ inexperienced surgeons. [18] The steep long learning curve is often discouraging to many surgeons who therefore declare the laparoscopic technique not worth for such a basic surgery. [19] 'Initially, the dissection of the extraperitoneal space in the TEP approach tended to be difficult, confusing and therefore hard to learn'.…”
Section: Introductionmentioning
confidence: 99%